The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/1286263
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hemorheology in Exacerbations of COPD

Abstract: Background Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow limitation. Cardiovascular-related comorbidities are established to contribute to morbidity and mortality especially during exacerbations. The aim of the current study was to determine alterations in hemorheology (erythrocyte aggregation, deformability) in newly diagnosed COPD patients and their response to medical treatment and to compare with values of COPD patients with exacerbations. Materials and Methods The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
7
0
2
Order By: Relevance
“…Less deformable erythrocytes generally have irregular shapes and do not return to their original shape easily, creating erythrocyte populations of different sizes and conformations. Indeed, some studies have shown lower erythrocyte deformability in COPD (Santini et al, 1997;Coppola et al, 1999;Ugurlu et al, 2017). As in animal model, a continuous reduction in deformability was associated with the progression of an inflammatory response (Silva-Herdade et al, 2016), the lower deformability of erythrocytes described in COPD may be due to the inflammatory condition of the disease, demonstrated in this study by means of increased leukocyte count and CRP values.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Less deformable erythrocytes generally have irregular shapes and do not return to their original shape easily, creating erythrocyte populations of different sizes and conformations. Indeed, some studies have shown lower erythrocyte deformability in COPD (Santini et al, 1997;Coppola et al, 1999;Ugurlu et al, 2017). As in animal model, a continuous reduction in deformability was associated with the progression of an inflammatory response (Silva-Herdade et al, 2016), the lower deformability of erythrocytes described in COPD may be due to the inflammatory condition of the disease, demonstrated in this study by means of increased leukocyte count and CRP values.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, this is consistent with the decrease in total and indirect bilirubin levels, which indicate a decrease in erythrocyte clearance (Memon et al, 2016), and with the lower levels of iron, which means the existence of a restrictive condition to erythropoiesis . Certainly, this predominance of more mature erythrocytes, which have less deformability, impairs the adequate supply of oxygen to the tissues, worsening the clinical condition of the patient with COPD, mainly in exacerbations of the disease (Ugurlu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased levels of MCHC could be linked to the deformation of red blood cells as indicated by the evaluated RDW-CV. A recent study in humans showed that MCHC levels were lower in a control (healthy) group than in a newly diagnosed COPD group (28). The process of hypoxia, induced by lower MCHC, may contribute to the lung tumor cell metastasis and poor prognosis (29).…”
Section: Immune and Hematological Traits Negatively Correlated With Lmentioning
confidence: 99%
“…Birçok klinik çalışmada, kan akışkanlığı ile kan dolaşımını da içeren çeşitli hastalıkların şiddeti arasındaki ilişki doğrulanmıştır. Çeşitli patolojik koşullarda, azalmış eritrosit deformabilitesi ve artmış eritrosit agregasyonu gibi akış davranışındaki değişikliklerin yanı sıra, plazma ve kan viskozitesinde de artışlar gösterilmiştir (8)(9)(10)(11). Bazı çalışmalar hemoreolojik değişikliklerin koklear vasküler tıkanıklık ile ilişkili olabileceğini rapor etmiştir (2, 12, 13).…”
Section: Introductionunclassified